The Image Of Women In Bangka Belitung Folk Tales - Elis Fitriani; Khoiriyatun Nisa; Windy Ikaluny; Alda Febrianti Z; Syafira Rizky P.; Elviona (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study examines the portrayal of women in folktales from the Bangka Belitung region through a feminist literary criticism approach grounded in Simone de Beauvoir’s existentialist theory. The research aims to identify how female characters are represented and how cultural values and gender ideology are embedded in these narratives. Employing a qualitative descriptive method, the study analyzes five folktales Asal Usul Penyusuk, Batu Balai, Kayu Kundi, Batu Belah Batu Betangkup, and Putri Mayang selected for their relevance to local cultural traditions. The findings reveal that women are predominantly depicted as compassionate, obedient, and self-sacrificing, reflecting patriarchal norms that define women’s roles within domestic and social spheres. Methodologically, the study integrates textual analysis and feminist interpretation to uncover ideological patterns within the stories. The significance of this research lies in demonstrating how folklore functions as a medium that both preserves cultural values and reinforces gendered power structures. The results offer important implications for gender-responsive literary education, highlighting the need for critical engagement with traditional narratives to promote more inclusive and equitable interpretations in contemporary learning contexts.